The Impact of Fedtugrow® Downstreaming with SPR Integration in Central Lampung Regency Using SROI - Farida Ratna Dewi; Ronald Tarigan; Fadjar Satrija; Muladno Muladno; Afton Atabany; Indah Wijayanti; Agik Suprayogi (Jurnal Ilmu Pertanian Indonesia, 2025)
The dissemination of research findings (innovation) in universities would have a social and economic impact on the larger community. IPB developed the depolarized katuk invention (known as Katulac), which was patented (P00201800110, Jan 5, 2018). IPB collaborated with the Local Government of Central Lampung Regency, PT Great Giant Livestock (GGL), and community farms named Hipermadani (downstreaming of university innovation for the community and farmers) in downstreaming Fedtugrow (innovation in combined livestock feed Katulac® and concentrate) to improve farmer welfare. Katulac®'s downstream innovation is the School for Smallholder Livestock Farming (Sekolah Peternakan Rakyat, SPR), an IPB innovation with copyright (EC00201987765, Nov 28, 2019). The Katulac® downstreaming initiative with SPR institutional integration resulted in a social investment of IDR 501,837,278 and a net social benefit of IDR1,488,959,391 for all stakeholders in the Hipermadani ecosystem. This program had a Social Return on Investment (SROI) of 2.97, which means that for every IDR 1 invested, it would deliver a social benefit of IDR 2.97, showing the program's success. Keywords: downstreaming, Hipermadani, innovation, Katulac, Social Return on Investment